2012
DOI: 10.1179/1743290112y.0000000020
|View full text |Cite
|
Sign up to set email alerts
|

From titanium to magnesium: processing by advanced metal injection moulding

Abstract: Metal Injection Moulding (MIM) is a good candidate for economic manufacturing of complex shaped components in high quantities. This is especially true for materials which are rather expensive and hard to form like titanium alloys. However, the high affinity to interstitial elements as oxygen and carbon presents a specific challenge with regard to powder purity, handling and sintering as well as to binder system and its removal. In this paper three examples for manufacturing high quality samples of advanced mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The results of this study have shown that it is possible to obtain properties using commercially developed gas atomised WE43 alloy that compare favourably with published values of extruded, forged and cast WE43B. Gas atomised Mg alloy powders with homogeneous fine scale microstructure and lower surface 6 Effect of gas pressure on microstructure of cold sprayed layer produced from gas atomised WE43 powder 7 Typical mechanical properties of PM consolidated WE43 alloy: 17,18 oxygen content lead to consolidated material with enhanced ductility relative to mechanically ground powder. Both atomised and ground powders can be successfully cold sprayed with acceptable levels of density using commercially available equipment, similar to what has been demonstrated using additive manufacturing using a coaxial powder feeder.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results of this study have shown that it is possible to obtain properties using commercially developed gas atomised WE43 alloy that compare favourably with published values of extruded, forged and cast WE43B. Gas atomised Mg alloy powders with homogeneous fine scale microstructure and lower surface 6 Effect of gas pressure on microstructure of cold sprayed layer produced from gas atomised WE43 powder 7 Typical mechanical properties of PM consolidated WE43 alloy: 17,18 oxygen content lead to consolidated material with enhanced ductility relative to mechanically ground powder. Both atomised and ground powders can be successfully cold sprayed with acceptable levels of density using commercially available equipment, similar to what has been demonstrated using additive manufacturing using a coaxial powder feeder.…”
Section: Discussionsupporting
confidence: 52%
“…Other magnesium powder based manufacturing processes in the early stages of investigation include additive manufacturing, 14 metal injection moulding (MIM), [15][16][17] cold spray, 18,19 and friction stir processing. 20 Additive manufacturing and MIM offer novel paths to fabricate intricate components, for example Mg alloy based bio-absorbable implants.…”
Section: Emerging Applications For Magnesium Alloy Powdersmentioning
confidence: 99%
“…), which increase impurities level and degrade sinterability without exception [1]. Overall, the β titanium alloys fabricated by binder-based powder technologies generally have more severe processing-related defects than those of common α/β-type Ti-6Al-4V alloy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some additives such as polymers and organic fibers were adopted. 12,13 A vacuum impregnating and resintering process was also developed to improve the high-temperature properties of Al 2 O 3 -based ceramic mold with micron-sized Y 2 O 3 additive. After the specimens were twice dipped into aqueous yttria sol in vacuum, the flexural strength at 1550 °C was increased to 3.5 MPa or so, which could not usually meet the requirement of the casting of gas turbine blade with large dimension.…”
Section: Introductionmentioning
confidence: 99%